Critical international political economy : dialogue, debate and d issensus - Shields, Stuart, 1966-; Bruff, Ian, 1978-; Macartney, Huw. (Houndmills, Basingstoke Hampshire ; New York : Palgrave Macmil lan, 2011)
"This book gives provocative responses to recent debates in Internat ional Political Economy. It provides a much needed and timely intervent ion to the current anodyne discussions about the evolution of the disci pline and prompts wider reflection on the nature of enquiry itself"--
Machine generated contents note: -- Introduction: 'Critical' and 'In ternational Political Economy'; S. Shields, I. Bruff & H. Macartney -- PART I: DIALOGUE -- Missing Voices: Critical IPE, Disciplinary History and H.N. Brailsford's Analysis of the Capitalist International Anarchy; L.M. Ashworth -- Space, the latest frontier? A scalar-relational appro ach to critical IPE; H. Macartney & S. Shields -- Poststructuralism in/ and IPE; P. Griffin -- PART II: DEBATE -- New Marxism and the Problem o f Subjectivity: Towards a Critical and Historical International Politic al Economy; R. Germain -- Overcoming the State/Market Dichotomy; I. Bru ff -- Critical Feminist Scholarship and IPE; J. Elias -- PART III: DISS ENSUS -- Reclaiming Critical IPE from the 'British' School; O. Worth -- 'What's Critical about Critical Theory?' Feminist Materialism, Interse ctionality and the Social Totality of the Frankfurt School; A. Fischer & D. Tepe -- Knowledge versus Power in the Field of IPE; P. Cammack -- Conclusion: IPE and the International Political Economy? IPE or the Int ernational Political Economy?; S. Shields, I. Bruff & H. Macartney.
Includes bibliographical references (p. 173-190) and index.
Keywords: International economic relations